2018
DOI: 10.1039/c8tc00145f
|View full text |Cite
|
Sign up to set email alerts
|

Two novel rhodamine-based molecules with different mechanochromic and photochromic properties in solid state

Abstract: Two novel molecules (AnRhB-1 and AnRhB-2) were synthesized using Rhodamine B and anthracene as building units via Schiff base chemistry with different spacers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 50 publications
0
26
0
Order By: Relevance
“…Therefore, it is of great significance to fabricate sensor materials with multiple functions to further widen the scope of application in different fields. [32][33][34][35][36][37] However, reports on such materials are very rare.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is of great significance to fabricate sensor materials with multiple functions to further widen the scope of application in different fields. [32][33][34][35][36][37] However, reports on such materials are very rare.…”
Section: Introductionmentioning
confidence: 99%
“…The pristine powder of 2a16 showed intense and sharp peaks, suggesting the crystalline state (Figure C). In contrast, the PXRD curve obtained by grinding showed lesser peaks, indicating that the powder had changed from the crystalline state to an amorphous one under the mechanical stress. After fuming the ground powder in acetone, some new peaks were detected. The minor differences in their PXRD curves of the fumed powder and the pristine powder indicated that the powder had changed from one crystalline phase to another, which was also consistent with their different emission spectra between the pristine powder and the fumed powder (Figure B).…”
Section: Resultsmentioning
confidence: 97%
“…In contrast, the PXRD curve obtained by grinding did not exhibit obvious peak, indicating that the pristine powder had changed from the crystalline state to an amorphous one after mechanical stress. [43][44][45][46] Upon fuming the ground powder in acetone, some new peaks appeared. The partly different PXRD curves of fumed powder compared to those of the pristine powder demonstrated the change from one crystalline phase to another, which was also consistent with their different emission spectral between pristine powder and fumed powder (Figure 6B).…”
Section: Aie Properties Of 2a16mentioning
confidence: 99%
“…[159,162,186,187] Interestingly, many of these systems could act sinergically with covalently-bound ones, yielding to more precise information about the mechanical history of the devices. [188] We summarized examples of the most common mechanoresponsive units found in the scientific literature in Figure 5, organizing them between those moieties that are covalently linked to polymers (Figure 5a) [169,170,[195][196][197][198][199][200][201]178,179,[189][190][191][192][193][194] and those molecules that are employed as dispersions in polymeric matrices (Figure 5b). [159,162,176,[202][203][204] The list is not exhaustive and for mechanochromic materials we address the reader to the comprehensive reviews of Sagara et al [150] and Chen et al [205] Moreover, several innovative molecular systems which can display different colors upon change of conformation or crystal structures, could expand the scope of mechanochromic materials in the near future, making more colorations available and improving the performances of the materials in terms of sensibility and reliability.…”
Section: From Cromatophore As Absorbance Elements Through Molecular Mechanochromic Devicesmentioning
confidence: 99%